Improvement of the technology of functional pre-made meat products in a dough shell - M. S. Nikolaenko (Тваринництво та технології харчових продуктів, 2021)
In modern conditions of increasing globalization and intensifying competition in the food industry in general and in the meat processing industry in particular, there is a need to find new ways to increase the competitiveness of enterprises, guarantee the quality and safety of products, ensure proper working conditions for personnel, and reduce the negative impact on the environment. The research aims to improve the technology of pre-made products in dough shell production and to determine the rational parameters of the production process by introducing new ingredients into the recipe. The content of toxic elements was determined based on the Ukrainian Laboratory of Quality and Safety of Agricultural Products of the National University of Life and Environmental Sciences of Ukraine. The main stages of production of pre-made products in dough shells were analyzed, the technology was improved considering a set of safety and quality studies, risks and critical control points, sources of their occurrence were identified, and preventive actions were developed. The amino acid composition of the protein component and functional and technological quality indicators of the minced meat samples (moisture retention capacity, emulsifying capacity, and stability of meat emulsions) were evaluated. To determine the changes that occurred in the experimental prepared products enriched with vegetable components, a study of changes in their physicochemical properties after freezing and thawing was conducted. The research results showed that in the experimental sample containing the food additive Elamin, the amount of bound moisture in meat systems gradually decreases during storage, but the mass fraction of the concentrate in the amount of 0.3 kg per 100 kg of raw material allows for retaining free moisture. Based on the research results, the technology of functional pre-made meat products in a dough shell was improved, and technical specifications and technological instructions state standard 10.1-00493706-075:2019 “Frozen semi-finished products in a dough shell “Healthy dumplings” were developed for implementation in production